PENGARUH KOMPETENSI DAN MOTIVASI PADA PENYERAPAN ANGGARAN BELANJA MODAL DENGAN KOMITMEN ORGANISASI PEJABAT PENGELOLA KEUANGAN SEBAGAI VARIABEL PEMODERASI - Imanuel Laka, Egidius; Sukartha, I Made; Wirama, Dewa Gede (E-Jurnal Ekonomi dan Bisnis Universitas Udayana; VOLUME.06.NO.12.TAHUN 2017, 2017)
The purpose of this study is to examine the influence of competence and motivation of financial management officials on the performance of capital expenditure absorption in local government of Timor Tengah Utara with organizational commitment as moderating variable. The population in this study is the work units (OPD) in Timor Tengah Utara regency government environment as much as 31 OPD. Sampling of the entire population is known by the technique of saturated samples or censuses. The number of respondents was 93 respondents. All respondents' answers to the research statement using questionnaires are the primary data used in this study. Hypothesis testing was done by multiple regression and moderation regression (MRA) Data used in the form of primary data using questionnaires. The analysis technique used are multiple regression and moderated analysis regression (MRA). The result of multiple regression analysis shows that competence and motivation of financial management officials proved have a positive effect on the performance of capital expenditure absorption, and moderated regression analysis shows that organizational commitment had no strengthen the influence of competence and motivation on capital expenditure absorption.